Diagnosis of the degree of maturity in lean manufacturing: case study in a wire and cable industry - Lopes, Manoel Isaac Teixeira Nunes; Sousa, Francisca Jociele Oliveira de; Teles, Francismilton; Albuquerque Neto, Hélio Cavalcanti; Almeida, Matheus das Neves; Pereira, Geordy Souza (Brazilian Journal of Production Engineering, 2024)
Companies use Lean Manufacturing (LM) practices; however, they have difficulties in measuring maturity to improve them and target goals. Given this context, the objective was to evaluate the maturity of the LM practices of a wire and cable company. To this end, the Maturity Assessment model was used, which measures 17 principles, divided into Structural Elements (SE): philosophy (3); processes (6); people and partners (5); problem solving and continuous improvement (3). In total, 6 managers and 21 employees from the operations and support areas responded to the questionnaires. The principles: create value for the customer; identify the value chain; use visual management; and see for yourself to understand the situation, converged at the same level of maturity between the groups. Furthermore, the operation’s employees had the lowest maturity level. Analyzing the SE, there was a positive emphasis on philosophy with grade 4 (integrated), while the others were classified as grade 3 (systematic), with the organization’s overall score at 3.80. Finally, the methodology used provided a set of objective goals for improving processes, identifying their strengths and weaknesses, allowing plans to be drawn up leading to organizational development.